PENGARUH KEMITRAAN, PELATIHAN, INTERNET DAN INOVASI TERHADAP PENDAPATAN INDUSTRI MIKRO KECIL DI PROVINSI SUMATERA BARAT - Imelfina Musthafa; Hefrizal Handra; Edi Ariyanto; Hafiz Rahman (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
This study aims to analyze the effects of partnerships, training, internet usage, and innovation on the income of Micro and Small Industries in West Sumatra Province. The study employs a quantitative approach using secondary data in the form of panel data. The cross-sectional unit of analysis covers 19 regencies/municipalities in West Sumatra Province, while the time-series dimension utilizes annual data for the period 2021–2023. The empirical analysis indicates that training, internet usage, and innovation have a statistically significant partial effect on income, whereas partnerships do not exhibit a significant effect. These findings suggest that training plays an important role in enhancing the capacity of Micro and Small Industries actors, while internet usage and innovation contribute to increasing Micro and Small Industries income in West Sumatra Province.